"Push–push and push–pull" polystannanes. Issue 39 (24th September 2018) - Dhindsa, J. S.; Jacobs, B. F.; Lough, A. J.; Foucher, D. A.
Abstract : Alternating "Push–pull" and "push–push" polystannanes prepared by condensation of tin diamides and tin dihydrides are described. Abstract : The synthesis and characterization of polystannanes with "push" or "pull" moieties attached to the tin backbone are described. Precursor tetra aryl- (1, 2 ) stannanes were converted to mono- (3 ) and dichloro- (4, 5 ) stannanes by either sequential chlorination or by redistribution reactions with SnCl4 . Compounds4 and5 were transformed to polymerisable tin dihydride monomers6 and7 using a large excess (10×) of NaBH4 . Homopolymer8 with electron donating aryl substituents ( p -MeOC6 H4 -) was synthesized by dehydrogenative polymerization using Wilkinson's catalyst. Attempts to prepare the homopolymer9 with electron withdrawing aryl substituents ( p -CF3 C6 H4 -) from the dehydrocoupling of7 using similar conditions led only to the formation of low molecular weight oligomeric species. Two alternating polymers, 10 and11, were synthesized by condensation polymerization of ( n -Bu)2 Sn(NEt2 )2 with monomers6 or7 . The first was a "push–push" alternating polymer, 10, comprised of a repeating unit consisting of two different electron donating groups ( p -MeOC6 H4 -, n -Bu) at neighboring tin centres. The second was a "push–pull" alternating polymer, 11, bearing both an electron donating group ( n -Bu) and a strongly electron withdrawing substituent ( p -CF3 C6 H4 -) at neighboring tin atoms. All small molecule stannanes and tin-containing polymers were characterized by NMR ( 1 H, 13 C, 119 Sn, and where required 19 F) spectroscopy, MS or EA. The absolute molecular weights of tin polymers (8, 10, 11 ) were determined by triple detection GPC and in the range of 1.07 × 10 4 to 1.95 × 10 4 Da. Rapid photodegradation of polymers was observed by UV-Vis spectroscopy, with a slower degradation observed for the "push–pull" polymer, 11, compared to the "push–push" polymer, 10 .